(untitled) (Belügyi Szemle, 2025)
Aim: The aim of the study is to model the offence of fiscal fraud (also known as VAT fraud) committed by exploiting the operating mechanism of the value added tax (VAT/statutory VAT) introduced in Hungary (by outlining its general and specific models) and to examine the possibility of its application in the investigative action of the authorities. Methodology: The topic was primarily addressed through secondary research, with a strong emphasis on the application of system thinking and criminological thinking, as well as best practices observed during the service as an investigator at the National Tax and Customs Administration (hereinafter: NAV) and conclusions drawn from case studies. Findings: If we accept the findings of the sources processed by the research and the conclusions drawn from them and from their further reflection, the three ‘building blocks’ of the general model of VAT fraud, i.e. the behaviour of the perpetrators, can be isolated on the basis of the VAT operating mechanism, namely: fraudulent deduction, concealment of income and concealment of operation. From these ‘building blocks’, the perpetrators typically build up complex cross-border structures in practice, which can be described by specific models based on their common features, in particular the specific participants and the invoicing/sales links between them. These specific models can also be considered as 'prefabricated' versions of investigations and, with due care, can be used effectively in the investigative action of the law enforcement authorities, although in practice they appear in more complex, distorted, mixed and sometimes renewed forms. Value: The value of the research lies in its approach to the VAT fraud offences in terms of systems, forensic thinking and best practice, and its integration into a coherent model that can be applied with due care and attention, but also effectively in the course of investigative action by the law enforcement authorities.